Synthesis, Characterization and Comparative Study of TiO2 and ZnO Nanoparticles and their Application as a Photocatalysts for a Trichromatic Dye - Kouhail, Meriem; Zakia, El Ahmadi; Abbes, Benayada (Current Nanomaterials, 2020)
Background: The textile industrial effluents cause profound imbalances in ecosystems, when released into nature; dyes are oxidized by micro-organisms, resulting in a decrease in the dissolved oxygen, which is necessary for the aquatic life. For this reason, it is important to implement economic, efficient, and green methods ensuring both the discoloration and detoxification of water. Objective: TiO2 and ZnO nanoparticles were synthesized by sol-gel and precipitation methods, respectively. These two nanoparticles were used to compare photocatalytic degradation under UV and solar irradiation for three reactive azoic dyes (trichromatic): Reactive Bezactive Yellow (RBY), Reactive Bezactive Red (RBR), and Reactive Bezactive Blue (RBB). Methods: The structural, i.e., morphological surface properties of the synthesized photocatalysts were characterized by Fourier Transform Infrared, X-ray diffraction, UV-Visible diffuse reflectance spectroscopy, and Scanning Electron Microscopy. X-ray diffraction shows that TiO2 has a tetragonal structure with an anatase form. The effects of some operational parameters, such as the amount of TiO2 and ZnO, initial dye concentration, dye mixtures, and pH, were examined. The progress of photodegradation reaction was monitored by UV-Visible spectroscopy for decolorization and by High-Performance Liquid Chromatography for degradation, and the efficiency of degradation was confirmed by Chemical Oxygen Demand measurement. Results: The dye degradation was found to be better in the presence of solar irradiation than under UV irradiation. The photocatalytic activity of ZnO was higher than TiO2 when used in its optimal conditions. Conclusion: The percentage of degradation of each dye is different, and the order of degradation of the three reactive dyes is as follows: RBY> RBR> RBB.
Keywords: trichromatic dye